On inverting gravity changes with the harmonic inversion method: Teide (Tenerife) case study - POHÁNKA, Vladimír; VAJDA, Peter; PÁNISOVÁ, Jaroslava (Contributions to Geophysics and Geodesy, 2015)
Here we investigate the applicability of the harmonic inversion method to time-lapse gravity changes observed in volcanic areas. We carry out our study on gravity changes occured over the period of 2004–2005 during the unrest of the Central Volcanic Complex on Tenerife, Canary Islands. The harmonic inversion method is unique in that it calculates the solution of the form of compact homogeneous source bodies via the mediating 3-harmonic function called quasigravitation. The latter is defined in the whole subsurface domain and it is a linear integral transformation of the surface gravity field. At the beginning the seeds of the future source bodies are introduced: these are quasispherical bodies located at the extrema of the quasigravitation (calculated from the input gravity data) and their differential densities are free parameters preselected by the interpreter. In the following automatic iterative process the source bodies change their size and shape according to the local values of quasigravitation (calculated in each iterative step from the residual surface gravity field); the process stops when the residual surface gravity field is sufficiently small. In the case of inverting temporal gravity changes, the source bodies represent the volumetric domains of temporal mass-density changes. The focus of the presented work is to investigate the dependence of the size and shape of the found source bodies on their differential densities. We do not aim here (yet) at interpreting the found solutions in terms of volcanic processes associated with intruding or rejuvenating magma and/or migrating volatiles.